2003
DOI: 10.1080/0967026031000085832
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature on the relationship between oxygen- and fluorescence-based estimates of photosynthetic parameters in a marine benthic diatom(Cylindrotheca closterium)

Abstract: In this paper we investigate the temperature sensitivity of the photosynthetic process of the benthic diatom Cylindrotheca closterium grown in light-limited turbidostat cultures at two different growth rates. Photosynthesis was measured as the rate of oxygen evolution and as the photosystem II (PSII) electron transport rate (ETR). The photosynthetic efficiency (a), as measured by both methods. was rather insensitive to temperature, and decreased significantly only at the extreme temperatures used (S and 3S'C).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
79
2
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 45 publications
12
79
2
1
Order By: Relevance
“…Numerous studies have also suggested that the reactions of dioxygen (O 2 ) and active oxygen species, such as the superoxide radical (O Á 2 ), the hydroxyl radical ( Á OH), hydrogen peroxide (H 2 O 2 ), and singlet oxygen (1Dg O 2 ), can cause photoinhibition of photosynthesis (Belay and Fogg, 1978;Cadenus, 2005;Foy and Gibson, 1982;Krause, 1994;Singh et al, 1995). Photosynthesis and photorespiration are also influenced by temperature, with higher temperatures increasing oxygenase and PSII activities (Belay and Fogg, 1978;Janssen et al, 2002;Morris and Kronkamp, 2003;Verity, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have also suggested that the reactions of dioxygen (O 2 ) and active oxygen species, such as the superoxide radical (O Á 2 ), the hydroxyl radical ( Á OH), hydrogen peroxide (H 2 O 2 ), and singlet oxygen (1Dg O 2 ), can cause photoinhibition of photosynthesis (Belay and Fogg, 1978;Cadenus, 2005;Foy and Gibson, 1982;Krause, 1994;Singh et al, 1995). Photosynthesis and photorespiration are also influenced by temperature, with higher temperatures increasing oxygenase and PSII activities (Belay and Fogg, 1978;Janssen et al, 2002;Morris and Kronkamp, 2003;Verity, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…A commonly used value for CF is 0.5 (Morris & Kromkamp 2003), implying that light is equally distributed between PSI and PSII. Hancke et al (2008) discuss the influence of the approach used to estimate the fraction of light absorbed by PSII when comparing PAM oxygen production estimates with those obtained from incubation experiments using different phytoplankton species.…”
Section: Discussionmentioning
confidence: 99%
“…However, some controversial results occur when P−I curves obtained from oxygen production incubation experiments are related to PAM-based estimates obtained under similar conditions e.g. with the macroalgae Porphyra columbina (Rhodophyta), Ulva australis (Chlo rophyta) and Zonaria crenata (Phaeophyta) (Franklin & Badger 2001); with the macroalgae U. rotundata, U. olivascens and P. leucosticta (Figueroa et al 2003); with the benthic diatom Cylindrotheca closterium (Morris & Kromkamp 2003); with phytoplankton (Goto et al 2008, Hancke et al 2008; with thin-and thick-leaved marine macroalgae (Nielsen & Nielsen 2008); and with phytoplankton (Blache et al 2011). The usefulness of chlorophyll fluorescence as a photosynthesis proxy depends on the existence of a predictable relationship with the quantum yield of oxygen or carbon dioxide evolution.…”
Section: Abstract: Photosynthesis−irradiance Relationship · Oxygen Imentioning
confidence: 99%
“…T let is the lethal temperature and the shape parameter β is a dimensionless parameter related to the Q 10 . To simplify curve fitting, Morris & Kromkamp (2003) fixed β at 1.3. We did not fix β, but we fixed T let as a function of experimental data.…”
Section: Culture Conditionsmentioning
confidence: 99%